2016
DOI: 10.3846/13926292.2016.1145152
|View full text |Cite
|
Sign up to set email alerts
|

Exact and Approximate Analytic Solutions of the Jeffery-Hamel Flow Problem by the Duan-Rach Modified Adomian Decomposition Method

Abstract: This paper aims to find the exact solution in an implicit form for the wellknown nonlinear boundary value problem, namely the MHD Jeffery-Hamel problem, which can be described as the flow between two planes that meet at an angle. Also, two accurate approximate analytic solutions (series solution) are obtained by the variation of the power series method (VPS) and the Duan-Rach modified Adomian decomposition method (DRMA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this study, a perturbation iterative scheme has been applied to find approximate analytical solutions to the nonlinear differential problems that govern Jeffrey-Hamel flow regarding heat transfer and viscous dissipation in nanofluids. The effect of active parameters such as nanoparticle volume friction, opening angle, Reynolds number, Prandtl number and Eckert number on velocity and temperature boundary layer thicknesses [31] have been examined [24]. Analytical approximate solutions are given and compared with Range-Kutta of fourth order scheme(RK4S), Differential Transformation method (DTM) [7], Homotopy Perturbation method (HPM) [8], Optimal Homotopy Asymptotic method (OHAM) [9], Spectral-Homotopy Analysis method (SHAM) [10], and Homotopy Analysis method(HAM) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a perturbation iterative scheme has been applied to find approximate analytical solutions to the nonlinear differential problems that govern Jeffrey-Hamel flow regarding heat transfer and viscous dissipation in nanofluids. The effect of active parameters such as nanoparticle volume friction, opening angle, Reynolds number, Prandtl number and Eckert number on velocity and temperature boundary layer thicknesses [31] have been examined [24]. Analytical approximate solutions are given and compared with Range-Kutta of fourth order scheme(RK4S), Differential Transformation method (DTM) [7], Homotopy Perturbation method (HPM) [8], Optimal Homotopy Asymptotic method (OHAM) [9], Spectral-Homotopy Analysis method (SHAM) [10], and Homotopy Analysis method(HAM) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these types of problems have been resolved with known semianalytical or numerical methods. These problems contain the Lattice-Boltzmann method, 20 He's variational iteration method (VIM) with the HPM, 21 the homotopy analysis method (HAM) with the homotopy perturbation method (HPM), and the differential transformation method (DTM), 22 the Adomian-decomposition method (ADM), [23][24][25][26][27] the Sumudu transform method, 28 Haar wavelet method. 29 The MHD Jeffery-Hamel flow with nanoparticle problem solved by using different numerical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The existence and uniqueness of the solution of (1.4) subject to (1.2) have been proved in [49]. Also, the numerical solutions to problems related to Blasius equations using the Adomian decomposition method can be found in [50,51]. The authors in [52] demonstrated that the solution for an arbitrary value of a can be obtained from the classical Blasius equation with a = 1 after a transformation.…”
Section: Introductionmentioning
confidence: 99%